The Influence of the Cooperative Learning Model of the Team Game Tournament (TGT) Type on Students' Collaborative Learning Abilities in the Indonesian Language Subject of Elementary School - Rambe, Khoirul Bariah; Nasution, Sahkholid (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
Previous studies on the Teams Games Tournament (TGT) learning model have primarily focused on cognitive aspects, such as learning outcomes and motivation. However, limited research has examined its effect on students' collaboration skills, particularly in the context of Indonesian language learning. This study aims to analyze the effect of the cooperative learning model of the TGT type on the collaboration skills of fifth-grade students at MIN 3 Labuhanbatu Selatan. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes, each with 26 students, selected through simple random sampling. Data were collected using questionnaires and observation sheets, and analyzed through normality tests, homogeneity tests, and the Mann-Whitney U test. The results indicate a significant difference between the experimental and control classes, with a significance value of 0.000 (< 0.05). The average post-test score of the experimental class was 75.92, while the control class scored 62.15. These findings demonstrate that the implementation of the TGT model significantly improves students' collaboration skills in Indonesian language learning.